2004
DOI: 10.1007/s11255-004-8869-9
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel density as a prognostic marker in bladder carcinoma: Correlation with tumor grade, stage and prognosis

Abstract: These data demonstrate that MVD in bladder carcinoma correlates with grade, stage and malignant potential of the tumor. Quantification of tumor angiogenesis may allow selection of the type of treatment for bladder cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 20 publications
3
28
1
1
Order By: Relevance
“…Moreover, angiogenic activity was correlated with a higher incidence of lymph node metastasis and poor prognosis for patients with transitional cell carcinoma of the bladder [22,23] . Mutational studies of the H-ras gene family have demonstrated that an alteration in codons 12 and 61 of the H-ras gene occurs in about 20% of bladder cancers [24] .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, angiogenic activity was correlated with a higher incidence of lymph node metastasis and poor prognosis for patients with transitional cell carcinoma of the bladder [22,23] . Mutational studies of the H-ras gene family have demonstrated that an alteration in codons 12 and 61 of the H-ras gene occurs in about 20% of bladder cancers [24] .…”
Section: Discussionmentioning
confidence: 97%
“…There is a long-standing controversy about whether a tumour's MVD can be used to indicate its grade [20][21][22]. Our data in the present study showed no significant difference in MVD values between well to moderately [23] found that the perfusion of well-differentiated HCC was distinct from those of moderately and poorly differentiated HCC, the difference may be due to the different patient population in their study including patients with unresectable or metastatic HCCs, and the timing of their dynamic CT was less than 30 s, in which their perfusion value came from the hepatic arterial perfusion and did not include hepatic portal perfusion; additionally, they categorised patients differently from those in our group.…”
Section: Discussionmentioning
confidence: 99%
“…Given that microvessel density, a surrogate marker for angiogenesis, correlates with progression and poor prognosis in invasive carcinomas of the bladder [10,11], the use of antiangiogenic therapies has started to be considered for bladder cancer patients [12]. This rationale has been also impelled by the recent and rapid development of therapies that selectively inhibit angiogenesis.…”
Section: Effects Of Bevacizumab On Autocrine Vegf Stimulation In Bladmentioning
confidence: 99%